A Model of Climate Belief Profiles: How Much Does It Matter If People Question Human Causation?. Issue 1 (14th May 2013) - Sibley, Chris G.; Kurz, Tim
<x xml:space="preserve">Abstract</x> Despite the weight of scientific evidence presented in recent assessment reports of the IPCC, there remains some skepticism among the public that the climate is changing and whether such change is caused by human activity. We modeled climate change belief profiles using Latent Class Analysis in a New Zealand national probability sample (N = 6, 072). Roughly 50% of New Zealanders believed that climate change was real and caused by humans, with 30% undecided. The majority of New Zealanders believe that climate change is real and likely caused by humans, with one in six remaining skeptical. We identified two types of climate skeptics, those who did not believe in climate change (7%), and those who believed climate change was real but not caused by humans (10%). Beliefs about the reality of climate change were more predictive than beliefs about human cause of support for carbon emissions policy and self‐reported proenvironmental behavior. Our model indicates that persuading people about the reality of climate change will predict greater incremental variance in behavior and policy attitudes than persuading people of its human cause; although persuading people of both will be still more effective due to the synergistic interaction of these dual beliefs.